PENERAPAN ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENENTUAN DOSEN BERPRESTASI BERDASARKAN TRIDHARMA PERGURUAN TINGGI - Zuchrotunisa; Sujatmiko, Bambang; Faizah, Arbiati (Inovate, 2020)
The assesment of lecturers’ performance to determine the outstanding lecturer is needed to know theresult of lecturers’ performance in doing all the teaching and learning process in the institution wherethe lecturers work. To obtain the lecturers’ highest ranking, the lecturers’ performance is evaluated byusing AHP. The software of decision support system is used with Analytical Hierarchy Process (AHP)consisting of three criteria: research, community service and some assessment indicators. The lecturersof technology and information faculty become the sample. After knowing the parameter. For the nextsteps, system requirement are analyzed, manipulating the knowledge, applying the method AnalyticalHierarchy Process and last but not least testing the system. The result of this research is an applicationthat can make the university assess the lecturers’ performance in the form of ranking become easier. Thehighest lecturer score of this research is 0.9343 that obtained from the system.Keywords: Decision Support System, AHP, Lecturers’ Performance